Uropathogens and their Culture Sensitivity Pattern in Children with Urinary Tract Infection. - Jamal, Muhammad Musarrat; Arif, Asad; Sarfaraz, Amna; Jamal, Javeria; Mahmood, Sohaib (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the frequency of bacteria causing Urinary Tract infections and their susceptibility to antibiotics in children of Sialkot.Study Design: Cross-sectional study.Place and Duration of Study: Department of Pediatrics Islam Teaching Hospital, Children Complex Hospital, and Islam Central Hospital, Sialkot Pakistan, from Jan to Dec 2020.Methodology: All patients presenting with Urinary Tract infections, aged one month to 15 years were included in the study. Inclusion criteria were clinical suspicion of Urinary Tract infections and positive urine culture of a single bacterium. Antibiotic susceptibility was performed on all culture-positive samples. Results: A total of 300 children were included, but 248 fulfilled the criteria of culture-positive Urinary Tract infections. Fiftytwo children were excluded as they had non-pathogen growths, multi-organisms or were already on antibiotics. Gramnegative bacilli were most frequently isolated, accounting for 236(95.2%), whereas Gram-positive cocci comprised only 12 (4.8%) of cases. E. coli was the most frequent isolate among gram-negative rods, followed by Klebsiella, Proteus and Pseudomonas. All gram-negative rods were sensitive to Imipenem, whereas most were resistant to Ampicillin and TMP-SMX. Gram-positive cocci were sensitive to Vancomycin, Linezolid, Meropenem and Tazobactam.Conclusion: Increasing resistance of uropathogens to commonly prescribed antibiotics is highly alarming. Therefore, the strategy of empirical treatment of Urinary Tract infections in children should be reevaluated based on regional studies.